Some determinants of the effects of VAL-5-angiotensin II amide on glomerular filtration rate and sodium excretion in dogs - McGiff, John C. (1969)
In 12 dogs anesthetized with chloralose, angiotensin (angiotensin II amide) given intravenously increased the glomerular filtration rate (GFR) of an ischemic kidney while simultaneously having little effect on the GFR of the contralateral kidney. In the ischemic kidney, in 14 of 30 observations, increments of GFR greater than 100% of mean control GFR (9 ml/min) occurred in response to angiotensin. The magnitude of the increase in GFR produced by angiotensin was independent of dose (range 0.005-0.050 μg/kg per min), the degree of accompanying pressor response, and alterations in renal blood flow (RBF) (electromagnetic flow-meter). In the ischemic kidney, increments of GFR could be produced by sub-pressor doses of angiotensin. Dissociations between increments of GFR and sodium excretion occurred. Equivalent increments of GFR in the ischemic kidney in dogs receiving either 5% glucose in water or 10% mannitol in 0.3% saline were associated with natriuresis only in the latter group: a) as an initial response of the contralateral kidney to renal arterial constriction (RAC) in spite of a concomitant reduction in RBF and an unchanged GFR; b) in the ischemic kidney on giving angiotensin. The natriuresis produced by angiotensin was independent of the magnitude of elevations in blood pressure, altered filtration fraction, and was associated with a further reduction in RBF. After release of RAC in the dogs receiving mannitol, an antinatriuresis was again observed in response to angiotensin. The presence of unilateral renal ischemia allowed the demonstration of a differential action of angiotensin on the GFR of an ischemic and nonischemic kidney. The natriuresis in response to angiotensin requires, in addition to mannitol, the participation of undefined factors invoked by unilateral renal ischemia.